Self-motivated effects of teachers’ supportive behaviors on students’ intentions of online continuous learning -- based on educational digital transformation - Zhiqun Ouyang; Xin Bai; Lin Huang; Qiang Li; Yingji Li (PLoS ONE, 2025)
The study explored the factors influencing students’ online continuous learning intentions (CLI) based on educational digital transformation (EDT). The theoretical model was based on the technology acceptance model (TAM), and two dimensions were proposed: flow experience (FE) and teachers’ supportive behaviors (TSBs). It studied how these variables directly or indirectly affected students’ intentions to CLI within EDT. The constructed model was validated by exploiting a partial least squares structural equation modeling approach (PLS-SEM) based on the valid data from 614 students from five private universities in China. The results suggested that (a) the construct TSBs, including teachers’ social support, teachers’ intellectual support, and teachers’ instrument support, had a positive impact on students’ intentions of online continuing learning within EDT; (b) perceived ease of use (PEU) had a positive effect on perceived usefulness (PU), flow experience (FE) and CLI; (c) perceived usefulness (PU) had an effect on FE and CLI; (d) flow experience (FE) had a positive effect on CLI. The findings offered valuable insights for academicians, higher institution administrators, researchers, and higher education policy-makers in enhancing students’ learning based on educational digital transformation.